PENINGKATAN KUALITAS PRODUK DAN PEMASARAN USAHA FAM’S KITCHEN UNTUK MENDUKUNG PERTUMBUHAN EKONOMI LOKAL - Pradnyani, I Gusti Agung Arista; Rahayu, Nila; Maryanti, Sri; Anwar, Adrianda; Genadi, Yeldy Dwi (Jurnal Abdimas Sangkabira, 2025)
Fam's Kitchen, as one of the MSMEs operating as a street vendor at night markets and concerts, faces problems related to the appearance of the unattractive place of sale and limited marketing strategies, both conventionally and digitally. This community service program aims to improve product quality and marketing strategies, especially by utilizing social media and improving the design of the place of business. Through training and mentoring, Fam's Kitchen is expected to be able to develop product quality, enhance the appearance of its place of sale, and maximize digital marketing. With these steps, it is hoped that this business can compete on a broader market, increase competitiveness, attract more customers, and contribute more broadly to local economic growth and empowerment of MSMEs.